The implementation of temporary endowment in Kuwait - Ab Rahman, Muhammad Firdaus; Amanullah, Muhammad (Al-Jami`ah, 2016)
Temporary waqf is a restricted endowment for a specific duration. This paper examines Kuwait Law of Waqf and the contemporary implementation of temporary waqf in Kuwait. The research shows that Kuwait law of waqf allowed the application of all types of waqf as temporary, the duration of waqf should not exceed sixty years and no more than two layers of generations. This paper proposes to encourage other Islamic countries to implement this concept of temporary waqf as an alternative benefit.